Phosphoprotein Phosphatase 1 but Not 2A Activity Modulates Coupled-Clock Mechanisms to Impact on Intrinsic Automaticity of Sinoatrial Nodal Pacemaker Cells - Syevda Tagirova Sirenko (MDPI AG, 2021)
Spontaneous AP (action potential) firing of sinoatrial nodal cells (SANC) is critically dependent on protein kinase A (PKA) and Ca2+/calmodulin-dependent protein kinase II (CaMKII)-dependent protein phosphorylation, which are required for the generation of spontaneous, diastolic local Ca2+ releases (LCRs). Although phosphoprotein phosphatases (PP) regulate protein phosphorylation, the expression level of PPs and phosphatase inhibitors in SANC and the impact of phosphatase inhibition on the spontaneous LCRs and other players of the oscillatory coupled-clock system is unknown. Here, we show that rabbit SANC express both PP1, PP2A, and endogenous PP inhibitors I-1 (PPI-1), dopamine and cyclic adenosine 3′,5′-monophosphate (cAMP)-regulated phosphoprotein (DARPP-32), kinase C-enhanced PP1 inhibitor (KEPI). Application of Calyculin A, (CyA), a PPs inhibitor, to intact, freshly isolated single SANC: (1) significantly increased phospholamban (PLB) phosphorylation (by 2–3-fold) at both CaMKII-dependent Thr17 and PKA-dependent Ser16 sites, in a time and concentration dependent manner; (2) increased ryanodine receptor (RyR) phosphorylation at the Ser2809 site; (3) substantially increased sarcoplasmic reticulum (SR) Ca2+ load; (4) augmented L-type Ca2+ current amplitude; (5) augmented LCR’s characteristics and decreased LCR period in intact and permeabilized SANC, and (6) increased the spontaneous basal AP firing rate. In contrast, the selective PP2A inhibitor okadaic acid (100 nmol/L) had no significant effect on spontaneous AP firing, LCR parameters, or PLB phosphorylation. Application of purified PP1 to permeabilized SANC suppressed LCR, whereas purified PP2A had no effect on LCR characteristics. Our numerical model simulations demonstrated that PP inhibition increases AP firing rate via a coupled-clock mechanism, including respective increases in the SR Ca2+ pumping rate, L-type Ca2+ current, and Na+/Ca2+-exchanger current. Thus, PP1 and its endogenous inhibitors modulate the basal spontaneous firing rate of cardiac pacemaker cells by suppressing SR Ca2+ cycling protein phosphorylation, the SR Ca2+ load and LCRs, and L-type Ca2+ current.